Tubercular Ulcer of Tongue in an Elderly Patient Masquerading as a Traumatic Ulcer - Ramesh Parajuli; Sushna Maharjan (Case Reports in Otolaryngology)
Tuberculosis is still one of the most prevalent diseases in developing countries like Nepal. However, due to the effectiveness of DOTS therapy, vaccination, and education, the prevalence of tuberculosis has fallen in recent years. Although the pulmonary and extrapulmonary tuberculosis, especially the tubercular lymphadenitis, is still very common in our country, the tuberculosis of oral cavity is an uncommon condition. We present a case of an elderly male who presented with the complaint of nonhealing ulcer of lateral border of tongue for 2-month duration which was masquerading as a traumatic ulcer due to sharp teeth adjacent to the lesion. Deep biopsy was taken under local anesthesia. Histopathological examination revealed that it was tuberculosis. Antitubercular therapy was then started which cured the lesion.